A Comparative Study of Senior Secondary School Boys And Girls To Their Adjustment And Socio-Economic Status. - Singh, Dr Indira; Narayan Tiwari, Dr.Prakash (Innovative Research Thoughts, 2017)
Adjustment is a necessary characterstic to be able to live peacefully in this world. Adjustment problem starts from the birth and continous till death. Adjustment is the process of arriving at the balanced state between the need of individual and their satisfaction. Home and school play a vital role in the adjustment of an individual. The learner adjusts actively in the school environment rather than passively adjusting to the school’s program. It is generally believed that children from high and middle socio-economic status parents are better exposed to a learning environment at home because of provision and availability of extra learning facilities. Socioeconomic status(SES) is an economically and sociological combined total measure of person’s work, experience and of an individual’s or family’s economic and social position in relation to others , based on income ,education, and occupational-when analysing family’s SES, the house hold income, learner’s education and occupation are examined as well as combined income. Researchers studied many researches o n the same topic and researcher found that the result of this study was different from area to area. To found the new results of adjustment and socio-economic status researcher obtain this topic for research.There would be 100 senior secondary students(50 boys, )